Policy efforts for the development of storage technologies in the US and Germany - Eric Borden; Wolf-Peter Schill (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Recent developments in electricity markets such as the increased deployment of variable renewable generation have prompted renewed interest over the role of energy storage. While storage technologies can in principle provide various benefits for the functioning of an electrical grid, many energy storage technologies are in initial stages of development and demonstration. The role of public policy is thus vital for development and market integration of storage technology. We identify and discuss selected policy efforts by the United States of America and Germany with a focus on less-developed storage technologies. While research and demonstration of storage technologies has increased in both countries, we find that public funding is still small compared to overall energyrelated expenditures. Both countries use technology-push and market-pull approaches. Whereas the U.S. focuses on technologies which are useful to improve system stability, like batteries, capacitors, and flywheels, Germany has a stronger focus on bulk seasonal storage that may aid the integration of variable renewables, for example power to gas. We conclude that increased data-sharing and cooperation between the two governments and research institutions will help enhance the efficacy of both countries' publicly funded storage research. U.S. research institutions that link basic research with commercialization of technology, as well as developments in U.S. regulation of ancillary markets, may provide useful models for Germany. The U.S., on the other hand, may look to Germany's institutions as inspiration for its loan guarantee program.
Keywords: Q38; Q42; Q48; 330; Energy Storage; Technology-Push; Market-Pull; U.S.; Germany